THE ROLE OF CORPORATE SOCIAL RESPONSIBILITY (CSR) FOR THE REMEDY OF AFFECTED PEOPLE IN CRIMES AGAINST HUMANITY CASE - Ainal Zahra Nabila (Student Journal of International Law, 2022)
In this study, ExxonMobil's Corporate Social Responsibility (CSR) programs are examined in order to investigate their role for the remedy of affected people in the crimes against humanity case that occurred in North Aceh. The methods that involved in this research is library research methods that describes the case, gathers, and organizes a wide variety of data from the document study (libraries) to produce a report about the role of CSR programs for the remedy of the affected people in crimes against humanity case committed by the party that is affiliated with the ExxonMobil, which is Indonesian National Armed Forces. In results, this research found that the role of CSR for the remedy of affected people in ExxonMobil crimes against humanity case can be handled by corporate citizenship, which is a limited concept of CSR, that comply with international guidance and standard of CSR.